FACTORS OF INFLUENCE ON PROFESSIONAL PREPARATION OF FUTURE PILOTS OF CIVIL AVIATION - Орленко H.; Веліченко M.; Шип, Л.; Старостіна, К. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
The article deals with the conceptual problems of pilot physical and psychological trainings, the importance of physical training of intended pilot of civil aviation, pay attention to the fact of health indicator topicality, specialists of aviation industry qualification, detection of elements and factors of flight trainings for increasing the quality and safety of flights, prove the fact that improvement of physical possibilities can lead to decreasing of air crash accidents and incidents. The development of one of the most important skills-endurance- facilitates systematic sports and doing special exercises. Physical training should be aimed at both the development of the physical component of health and the improvement of the organism’s stability to difficult work conditions. Increasing the level of concentration, increasing the speed of the reaction and improving the speed of decision making, health promotion and the prevention of chronic diseases can be achieved by systematic sports, observance of the rules of the day and right nutrition. An important condition for professional training of the body of pilots to overload during the conduct of experiments was found that the adverse effect on the body of overloads is accompanied by a number of compensatory reactions. To reduce the negative impact of overload on the body was developed a set of exercises, which contributes to the improvement of compensatory mechanisms. These include running, aerobics, swimming, elements of sailing and other exercises that require intensive work of the cardiovascular and respiratory systems and also bring speed endurance. It has been experimentally proved that the systematic use of such complex of exercises among civil aviation pilots who have experienced the maximum overload showed much better results than those who did not use this complex. No less important role in physical training play trainings on special stands, such as rotary swings and centrifuge. The process of physical training emphasizes the training of endurance, makes it possible to improve positive influence on psychological state of pilots, maintain high indexes of state of health that will provide the flight safety